Pathophysiological Role of Synovitis in Hemophilic Arthropathy Development: A Two-Hit Hypothesis - Calcaterra, Ilenia; Iannuzzo, Gabriella; Dell’Aquila, Francesco; Di Minno, Matteo Nicola Dario (Frontiers in Physiology, 2020)
Despite an increasing access to prophylaxis with clotting factor concentrates, arthropathy still represents the main chronic complication of haemophilia. Whereas previous studies described haemophilic arthropathy as a degenerative arthropathy, somehow resembling osteoarthritis, most recent evidence suggests that complex inflammatory and immunologic mechanisms are also involved in the pathophysiology of haemophilic arthropathy. In the present review we described available data on major mechanisms leading to arthropathic changes in patients with haemophilia, with a specific focus on the role of synovium. The presence of hemosiderin in the joint space induces synovium proliferation, thus leading to formation of several lytic enzymes determining chondrocytes apoptosis and proteoglycans levels reduction. This leads to a direct joint “chemical” damage representing early damages in the pathogenesis of HA (first hit). In parallel, synovial membrane and synovial endothelial cells, become a dynamic reservoir of inflammatory cells and mediators, and propagate the inflammatory response (second hit), switching the process from a chemical damage to an inflammatory damage. Overall, consistent data pointed out synovitis as the keystone in haemophilic arthropathy pathophysiology. This opens novel potential therapeutic targets in this clinical setting.